Novel pH-sensitive drug-loaded electrospun nanofibers based on regenerated keratin for local tumor chemotherapy. Issue 19 (October 2020) - Zhang, Jing; Li, Jiashen; Xu, Chengshu; Xi, Zhihua; Ren, Yan; Song, Qingwen; Lu, Shaofeng
The present work developed keratin-based pH-sensitive nanofibers and explored the kinetics of the controlled-release effect. Extracted from wool fibers, keratin was firstly synthesized with 5- fluorouracil (5-FU). Then 5-FU/keratin was blended with poly (L-Lactide) PLLA solution and electrospun altogether to fabricate a nanofibrous scaffold, for local tumor chemotherapy. 5-FU/keratin/PLLA nanofibrous scaffolds were characterized by Fourier transform infrared spectroscopy to confirm that 5-FU was loaded within the nanofibers successfully. Scanning electron microscopy and transmission electron microscope images indicated the smooth and uniform structure of the nanofibers. Thermo-gravimetric analysis differential scanning calorimeter and X-ray diffraction techniques indicated 5-FU particles distributed in nanofibers at a molecular level. Compared with 5-FU from pure drug and 5-FU/PLLA nanofibers without keratin, the dissolution results indicated that 5- FU/keratin/PLLA nanofibers had a pH-stimuli responsive character in the acidic environment. HCT-116 tumor cell line was applied to investigate the antitumor effect of the composite nanofibers. The MTS assay indicated that adding keratin into the system increased the inhabitation of tumor cells after 120 hours observation. Zeta potential analysis was introduced to analyze the interaction effect between 5-FU and keratin. The in vitro drug release kinetics analysis indicated that due to the electrostatic interaction between keratin and 5-FU molecules, the composite nanofibers can extend the release period of 5-FU in the acidic environment which suggested a longer effective inhibition in local tumor chemotherapy.